2016
DOI: 10.1038/ncomms10572
|View full text |Cite
|
Sign up to set email alerts
|

Common and rare variants associating with serum levels of creatine kinase and lactate dehydrogenase

Abstract: Creatine kinase (CK) and lactate dehydrogenase (LDH) are widely used markers of tissue damage. To search for sequence variants influencing serum levels of CK and LDH, 28.3 million sequence variants identified through whole-genome sequencing of 2,636 Icelanders were imputed into 63,159 and 98,585 people with CK and LDH measurements, respectively. Here we describe 13 variants associating with serum CK and 16 with LDH levels, including four that associate with both. Among those, 15 are non-synonymous variants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 57 publications
3
49
0
Order By: Relevance
“…In an Icelandic cohort of 63 159 individuals, the reported allele frequency was 0.0215. 2 Consistent with previous reports, 2,12 Siddiqui et al 11 found that the association between CKM Glu83Gly and CK levels is independent of statin use.…”
Section: See Article By Siddiqui Et Alsupporting
confidence: 87%
See 1 more Smart Citation
“…In an Icelandic cohort of 63 159 individuals, the reported allele frequency was 0.0215. 2 Consistent with previous reports, 2,12 Siddiqui et al 11 found that the association between CKM Glu83Gly and CK levels is independent of statin use.…”
Section: See Article By Siddiqui Et Alsupporting
confidence: 87%
“…This is consistent with a previous observation that this genetic variant is not associated with statin intolerance. 2 Nevertheless, it is important to highlight that in JUPITER, as in most randomized controlled double-blind trials and observational studies, 5,15 no dedicated questionnaire to query patients systematically about muscle complaints was used. Alas, it has become apparent during recent years that the difficulty in identifying genetic risk factors of statin-induced myalgia may lie in the lack of precision in defining it compared with more severe manifestations, such as rhabdomyolysis.…”
Section: De Denus Et Al Ck and Precision Medicinementioning
confidence: 99%
“…23 The minor allele frequency (MAF) in the Canadian study was 0.010. 23 Kristjansson et al 4 replicated these findings in a genome-wide association study performed on 63 159 Icelanders with CK measurements. They report the main effect of the CKM Glu83Gly variant as being associated with serum CK (β=−0.446, P value=1.8×10 −115 ).…”
Section: See Editorial By De Denus Et Al See Clinical Perspectivementioning
confidence: 80%
“…The MAF in the Icelandic cohort was 0.0215. 4 Given the robust association and biologically apparent role of the gene in the production of CK, we wanted to gain insight into the relationship between the variant and CK response. Because CK elevations in response to appropriate stressors is the clinically significant feature of the biomarker, we sought to understand the impact of the variant on inducibility of CK.…”
Section: See Editorial By De Denus Et Al See Clinical Perspectivementioning
confidence: 99%
“…Myocardial enzymes, CK and LDH, are commonly used markers of myocardial injury (Kristjansson et al, 2016). To evaluate the degree of myocardial injury, the activities of CK and LDH were detected using commercial kits.…”
Section: Discussionmentioning
confidence: 99%